Development of Visionary Leadership in Public Service: A Visionary Leadership Model in the Development of the Efarina University Library's User Education Program Based on Digital Literacy - Nur Marliana Harum Harahap; Endang Fatmawati; Herman Herman; Sukardo Sitohang; Desi Sijabat; Natalina Purba; Rahmawati Rahmawati (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
Visionary leadership has a strategic role in the development of library services, especially in facing the challenges of digital transformation and the increasing need for user information literacy. This study aims to analyze a visionary leadership model in the development of digital literacy-based library user education programs at the Efarina University Library. This study uses a qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews with library leaders and librarians, as well as analysis of library program and policy documents. The results of the study show that the application of visionary leadership contributes significantly to the planning, implementation, and evaluation of digital literacy-based user education programs. Library leaders play the role of agents of change through the formulation of adaptive visions, strengthening the competence of librarians, utilizing information technology, and collaborating with the academic community. The user education program developed not only improves users' ability to access and evaluate digital information sources, but also encourages optimal use of library services. This study concludes that the visionary leadership model is a key factor in the successful development of digital literacy-based user education programs in the university library environment.